Internet filtering in China - Zittrain, J.; Edelman, B. (IEEE internet computing, 2003)
We collected data on the methods, scope, and depth of selective barriers to Internet usage through networks in China. Tests conducted from May through November 2002 indicated at least four distinct and independently operable Internet filtering methods - Web server IP address, DNS server IP address, keyword, and DNS redirection with a quantifiable leap in filtering sophistication beginning in September 2002.